Are high- and low-molecular-weight sensitizing agents associated with different clinical phenotypes of occupational asthma? - Vandenplas, Olivier; Godet, Julien; Hurdubaea, Laura; Rifflart, Catherine; Suojalehto, Hille; Wiszniewska, Marta; Munoz, Xavier; Sastre, Joaquin; Klusackova, Pavlina; Moore, Vicky; Merget, Rolf; Talini, Donatella; et al. (Allergy, 2019)
BACKGROUND: High-molecular-weight (HMW) proteins and low-molecular-weight (LMW) chemicals can cause occupational asthma (OA) although few studies have thoroughly compared the clinical, physiological, and inflammatory patterns associated with these different types of agents. The aim of this study was to determine whether OA induced by HMW and LMW agents shows distinct phenotypic profiles. METHODS: Clinical and functional characteristics, and markers of airway inflammation were analyzed in an international, multicenter, retrospective cohort of subjects with OA ascertained by a positive inhalation challenge response to HMW (n = 544) and LMW (n = 635) agents. RESULTS: Multivariate logistic regression analysis showed significant associations between OA caused by HMW agents and work-related rhinitis (OR [95% CI]: 4.79 [3.28-7.12]), conjunctivitis (2.13 [1.52-2.98]), atopy (1.49 [1.09-2.05]), and early asthmatic reactions (2.86 [1.98-4.16]). By contrast, OA due to LMW agents was associated with chest tightness at work (2.22 [1.59-3.03]), daily sputum (1.69 [1.19-2.38]), and late asthmatic reactions (1.52 [1.09-2.08]). Furthermore, OA caused by HMW agents showed a higher risk of airflow limitation (1.76 [1.07-2.91]), whereas OA due to LMW agents exhibited a higher risk of severe exacerbations (1.32 [1.01-1.69]). There were no differences between the two types of agents in the baseline sputum inflammatory profiles, but OA caused by HMW agents showed higher baseline blood eosinophilia and a greater postchallenge increase in fractional nitric oxide. CONCLUSION: This large cohort study describes distinct phenotypic profiles in OA caused by HMW and LMW agents. There is a need to further explore differences in underlying pathophysiological pathways and outcome after environmental interventions.
Keywords: dospělí; odds ratio; Female; biologické markery; Biomarkers; Adult; Allergens; ženské pohlaví; asthma; počet leukocytů; lidé; Occupational Exposure; bronchial provocation tests; occupational diseases; imunizace; Immunization; profesionální astma; phenotype; retrospektivní studie; Leukocyte Count; molekulová hmotnost; Male; pracovní expozice; Asthma, Occupational; alergeny; lidé středního věku; Respiratory Function Tests; mužské pohlaví; respirační funkční testy; Molecular Weight; Retrospective Studies; Middle Aged; Odds Ratio; Humans